Building locally anchored implementation science capacity: the case of the adolescent HIV implementation science alliance-supported local iS alliances - Vorkoper, Susan; Agot, Kawango; Dow, Dorothy E.; Mbizvo, Michael; Mugo, Cyrus; Sam-Agudu, Nadia A.; Semitala, Fred C.; Zanoni, Brian C.; Sturke, Rachel (Frontiers in Health Services, 2024)
BackgroundThe Fogarty International Center-led Adolescent HIV Implementation Science Alliance (AHISA) supports region-/country-specific implementation science (IS) alliances that build collaborations between research, policy, and program partners that respond to local implementation challenges. AHISA supported the development of seven locally-led IS alliances: five country-specific (i.e., Kenya, South Africa, Tanzania, Uganda, and Zambia), one in Central and West Africa, and one with youth researchers. This article outlines the aims, activities, and outcomes of local alliances, demonstrating how they enhance sustainable IS activities to address local challenges.MethodsWe conducted a desk review of each alliance's funding applications, reports, and data from the initial findings of a larger AHISA evaluation. The review analyzes common approaches, highlights their local relevance, and summarizes initial outcomes.ResultsThe local alliances have a common goal: to expand implementation of successful interventions to improve adolescent HIV. We identified four overarching themes across the local alliances’ activities: capacity building, priority setting, stakeholder engagement, and knowledge dissemination. Research capacity building activities include long-term mentorship between junior and senior researchers and short-term training for non-research partners. Setting priorities with members identifies local research needs and streamlines activities. Alliances incorporate substantial engagement between partners, particularly youth, who may serve as leaders and co-create activities. Dissemination shares activities and results broadly.ConclusionLocal IS alliances play a key role in building sustainable IS learning and collaboration platforms, enabling improved uptake of evidence into policy and programs, increased IS research capacity, and shared approaches to addressing implementation challenges.